Fluorine-containing polyimide composite humidity-sensitive material as well as preparation method and application thereof
Through low -temperature synthesis and chemical amine -containing composite moisture -containing moisture -containing fluoride, solving the problem of inaccurate measurement of existing humidity sensors in low humidity and high humidity environment, and achieve higher stability and accuracy of measurement accuracy sex.
Patent Information
- Application Number
- CN202411439880.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-28
AI Technical Summary
The existing humidity sensors are inaccurate in low-humidity and high-humidity environments, and have poor pollution resistance and short life. The preparation process of fluoropolymer-containing polyimide films of high molecular humidity sensors is complex and costly, and the hydrolysis of imine rings leads to measurement deviations.
The two -step method of low -temperature synthesis containing fluoride containing fluoride is used to prepare powder -containing fluoride amine powder through chemical amine, and mixed with nano -silicon dioxide to prepare composite wet sensitivity materials. This method does not require high -temperature amine, avoiding thin film contraction and air pores caused by water molecules from separating.
Reduce the humidity absorption rate, improve the processing performance, reduce the dampness of the humidity sensor, reduce the humidity deviation, and improve the stability of the sensor and measure the accuracy.
Smart Images

Figure CN119371659A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a fluorine-containing polyimide composite humidity-sensitive material, a preparation method thereof, and an application thereof in a sensor. Background Art
[0002] With the development of modern science and technology, the requirements for humidity measurement in scientific research, agriculture, meteorology, textiles, aerospace, electricity and other industrial sectors are increasing. At present, there are three main types of humidity sensors commonly found on the market: ion humidity sensors, ceramic humidity sensors, and polymer humidity sensors. The main disadvantage of ion humidity sensors is that the resistance value does not change significantly with temperature under low humidity and high humidity conditions, so they cannot be used for measurements in low humidity and high humidity environments, and they have weak anti-pollution capabilities and generally short lifespans. Ceramic humidity sensors have low sensitivity and poor linearity under low humidity conditions. Moreover, the consistency of ceramic humidity sensor products is generally poor, making it difficult to mass-produce. Therefore, polymer humidity sensors have gradually become the mainstream of humidity sensor research and manufacturing due to their rich material sources, low prices, simple manufacturing processes, good product consistency, wide applicable temperature range, wide application range, and short response time.
[0003] Polymer humidity sensors are generally divided into resistive and capacitive types. Resistive humidity sensors are a type of sensor that uses the resistance of polymer electrolytes to change with humidity to measure ambient humidity. This type of sensor has the advantages of high humidity sensitivity, good linearity, short response time, and good resistance to high humidity. However, it cannot be used for measurements in low-humidity and high-humidity environments, is not resistant to pollution, and its resistance is affected by the electrolyte in the environment, and generally has a short lifespan. The hygroscopic material of the capacitive humidity sensor adsorbs and releases water molecules in proportion to the relative humidity of the surrounding environment. Most of these polymer materials are dielectrics with a small dielectric constant (ε=2~7), while the dielectric constant of water molecules with a dipole moment can reach more than 80. When the ambient humidity changes, the dielectric constant of the capacitor of the hygroscopic material changes, and the capacitance changes. The physical quantity of humidity change reflected by the capacitance change is relative humidity.
[0004] Polyimide is one of the organic polymer materials with good comprehensive performance. It has good electrical properties, small dielectric constant, good wear resistance, excellent chemical stability at extreme temperatures and a series of excellent properties. Using polyimide as a humidity sensing film to make a capacitive humidity sensor has many advantages such as fast response speed, high sensitivity, wide output range and good long-term stability.
[0005] Guangzhou Aosong Electronics Co., Ltd. provides a capacitive humidity sensor in its invention patent application with publication number CN115201284A and titled "A Capacitive Humidity Sensor and Its Preparation Method". It uses a high molecular weight fluorinated polyimide film as a humidity-sensitive film, and uses the strong hydrophobicity and low molar polarizability of fluorine atoms to improve the moisture absorption rate, dielectric constant and other properties of the humidity sensor; thus, the purpose of reducing the humidity stagnation of the humidity sensor and reducing the humidity deviation is achieved, and the stability and measurement accuracy of the humidity sensor are improved. However, the fluorinated polyimide film used in it needs to first form a polyamic acid precursor under a vacuum state, and then use a staged gradient high-temperature heating treatment for imidization treatment, so that the preparation method of the fluorinated polyimide film is relatively strict, the process is complex and the cost is high. In addition, the fluorinated polyimide film is used as a humidity-sensitive film, and the imide ring therein will hydrolyze, resulting in a large measurement deviation of the sensor. Therefore, when the above-mentioned fluorinated polyimide film is used in the sensor, a layer of protection needs to be formed on its surface to avoid the influence of external liquids, moisture, chemicals, etc. on the performance of the humidity-sensitive film. Summary of the invention
[0006] In view of this, it is necessary for the present invention to provide a fluorinated polyimide composite humidity-sensitive material with low cost, simple process and good stability, and a preparation method thereof and application in sensors to solve the above problems.
[0007] Specifically, the technical solution provided by the present invention is as follows: A method for preparing a fluorinated polyimide composite humidity-sensitive material comprises the following steps: Synthesis of polyamic acid: dissolving diamine, dianhydride and fluoride in a non-protonic polar solvent, and subjecting the dianhydride, diamine and hexafluoropropane to a low-temperature polycondensation reaction under a nitrogen atmosphere to obtain a polyamic acid solution, wherein the fluoride is hexafluoropropane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl; Chemical imidization: adding a catalyst to the polyamic acid solution to continue the reaction to obtain a fluorinated polyimide powder; Preparation of the composite humidity-sensitive material: dissolving the fluorinated polyimide powder in an organic solvent, adding silicon dioxide nanoparticles and mixing thoroughly to obtain the composite humidity-sensitive material.
[0008] The preparation method of the composite humidity-sensitive material provided by the present invention uses diamine or dianhydride containing fluorine groups and hydroxyl groups as monomers and adopts a two-step synthesis method to prepare the composite humidity-sensitive material. The use of the composite humidity-sensitive material to prepare a capacitive humidity sensor does not require high-temperature imidization or the removal of water molecules from its molecular structure, will not cause shrinkage of the film, and will not form pores on the surface of the thin film device, thereby destroying the structure of the sensitive film and affecting the performance of the sensor.
[0009] The present invention also provides a fluorine-containing polyimide composite humidity-sensitive material prepared by the above-mentioned preparation method. The fluorine-containing polyimide composite humidity-sensitive material is mainly composed of a uniform mixture of fluorine-containing polyimide and nano-silicon dioxide, wherein the main chain of the polyimide is a hydrophobic skeleton and contains hydrophilic groups such as carbonyl and carboxyl groups that can adsorb water molecules. The hydrophilic groups have strong hydrogen bonds with the adsorbed water molecules, making it difficult for the water molecules to desorb. The introduction of hydrophobic fluorine atoms into the composite humidity-sensitive material can weaken the coagulation of water molecules, reduce the density of hydrophilic groups, reduce the wet hysteresis of the humidity-sensitive material, and make the capacitance output linear. At the same time, the introduction of fluorine atoms can increase the distance between molecular chains, reduce the intermolecular forces, make it easier for solvent molecules to diffuse into the material, improve the solubility performance, and improve the processability of the composite humidity-sensitive material; in addition, the introduction of silicon dioxide nanoparticles with a large specific surface area into the composite humidity-sensitive material can make the humidity-sensitive material adsorption-desorption equilibrium speed fast, accelerate the response speed, and improve the humidity sensing performance.
[0010] Therefore, the fluorinated polyimide composite humidity-sensitive material provided by the present invention has strong hydrophobicity and low molar polarizability, can effectively reduce the moisture absorption rate of the humidity-sensitive film, improve processing performance, reduce the hygroscopicity of the humidity sensor, and reduce humidity deviation.
[0011] The present invention also provides an application of the above-mentioned fluorinated polyimide composite humidity-sensitive material in a humidity-sensitive sensor. The fluorinated polyimide composite humidity-sensitive material is used as a humidity-sensitive film in a capacitive humidity sensor, has good linearity, and has better performance than traditional humidity-sensitive materials, and can effectively improve the measurement accuracy, stability and reliability of the humidity sensor. The humidity deviation of the capacitive sensor using the above-mentioned fluorinated polyimide composite humidity-sensitive material after being treated with double 85 for 10 days does not exceed 1%, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is an EDS image of the fluorinated polyimide composite humidity-sensitive material provided in Example 2 of the present invention; Figure 2 The figure is a result diagram of the effect of diamine on the fluorinated polyimide composite humidity-sensitive material, wherein Figures (a), (b), and (c) represent the humidity response results of the humidity-sensitive materials provided in Example 2 and Comparative Example 1-2, respectively; Figure 3 This is the result diagram of the effect of the amount of nano-silicon dioxide on the performance of fluorinated polyimide composite humidity-sensitive materials; Figure 4 The high temperature and high humidity stability test diagram of the capacitive humidity sensor provided in the embodiment of the present invention, wherein Figures (a), (b), and (c) represent the high temperature and humidity response results of the capacitive humidity sensors provided in Application Example 2, Application Comparison Example 1, and Application Comparison Example 3, respectively. DETAILED DESCRIPTION
[0013] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0014] Unless otherwise specified, the terms used in the present invention are commonly used terms in the relevant field. The raw materials, equipment, preparation processes, testing methods, etc. used are all prior arts in the relevant field unless otherwise specified. The reagents and products used are also commercially available. The sources and trade names of the reagents used, as well as their components, if necessary, are indicated when they first appear.
[0015] The present invention mainly uses the chemical imidization method to prepare fluorinated polyimide. First, diamine or dianhydride containing fluorinated groups and hydroxyl groups is used as a monomer and the ratio of the two is controlled. The fluorinated polyimide is synthesized at low temperature by a two-step method without high-temperature imidization. Then, the doping ratio of silicon dioxide nanoparticles and the fluorinated polyimide is controlled to obtain a fluorinated polyimide composite humidity-sensitive material. The fluorinated polyimide composite humidity-sensitive material can improve the humidity sensing performance of the humidity sensor.
[0016] Specifically, the present invention provides a method for preparing a fluorinated polyimide composite humidity-sensitive material, comprising the steps of: Synthesis of polyamic acid: dissolving diamine, dianhydride and fluoride in a non-protonic polar solvent, and subjecting the dianhydride, diamine and 2,2-bis(3-amino-4-hydroxyphenyl)-bishexafluoropropane to a low-temperature polycondensation reaction under a nitrogen atmosphere to obtain a polyamic acid solution, wherein the fluoride is hexafluoropropane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl; Chemical imidization: adding a catalyst to the polyamic acid solution to continue the reaction to obtain a fluorinated polyimide powder; Preparation of the composite humidity-sensitive material: dissolving the fluorinated polyimide powder in an organic solvent, adding silicon dioxide nanoparticles and mixing thoroughly to obtain the composite humidity-sensitive material.
[0017] The step of synthesizing polyamic acid is mainly to obtain a polyamic acid solution by a low-temperature polycondensation reaction of dianhydride, diamine and the fluoride in a non-protonic polar solvent. Specifically, the diamine and 2,2-bis(3-amino-4-hydroxyphenyl)-bishexafluoropropane are first dissolved in the non-protonic polar solvent, and then the dianhydride is added in multiple times, and the time interval between two adjacent additions of the dianhydride is 5-15 minutes, and the polyamic acid is synthesized by stirring the reaction in a nitrogen atmosphere ice water bath for 22-24 hours to obtain the polyamic acid solution. Preferably, the ice water bath temperature is 0-5 ℃.
[0018] Among them, in order to make the composite humidity-sensitive material have better high-temperature stability, reduce hysteresis, and improve response speed and humidity sensing performance, in the process of synthesizing polyamic acid, the molar ratio of the diamine, dianhydride and fluoride is preferably 2:1:(0.95-1.05).
[0019] Different dibasic anhydrides have different electron affinities, and different diamines have different alkalinity. The process of the two reacting to form polyamic acid is a reversible process, and the electron affinity and alkalinity determine the equilibrium constant of the reversible reaction; in addition, polyamic acid with a long molecular chain and a high molecular weight has better mechanical properties. Therefore, the diamine is preferably 4,4'-methylenebis(2,6-diethylaniline), 4,4'-biphenylenediamine or p-phenylenediamine, and the dianhydride is preferably 4,4'-oxydiphthalic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride or biphenyltetracarboxylic anhydride.
[0020] In order to make the polyamic acid more soluble, the aprotic polar solvent is preferably one or two of N-methylpyrrolidone, dimethylacetamide, and N,N-dimethylformamide.
[0021] The chemical imidization step includes: adding the catalyst to the polyamic acid solution, continuing to stir the reaction in a nitrogen atmosphere ice water bath for 22-24 hours to fully imidize the polyamic acid, adding anhydrous ethanol to obtain a light yellow viscous product; filtering and vacuum drying the light yellow viscous product to obtain a fluorinated polyimide powder. The vacuum drying temperature is 70-100°C. The catalyst is acetic anhydride and 3-methylpyridine, and the molar ratio is preferably (2.5-3.5):1.
[0022] In order to effectively reduce the moisture absorption rate of the humidity-sensitive material and improve the response sensitivity of the humidity-sensitive material, the particle size of the silicon dioxide nanoparticles is preferably 20-50 nm, the mass ratio of the fluorinated polyimide to the silicon dioxide nanoparticles is preferably 10: (0.95-1.05), and the solid-liquid ratio of the fluorinated polyimide to the organic solvent is 1: (4-5) g / mL. Among them, if the organic solvent remains in the humidity-sensitive material, it will affect the humidity sensing performance of the humidity-sensitive material. Therefore, the organic solvent is basically volatilized during the film-forming process. Preferably, the organic solvent is any combination of one or more of N, N-dimethylformamide, N, N-dimethylacetamide, and tetrahydrofuran.
[0023] In order to simplify the preparation process of the humidity sensor, the steps of preparing the composite humidity sensitive material include: dissolving the fluorinated polyimide powder in the organic solvent to form a fluorinated polyimide solution; adding the silicon dioxide nanoparticles to the fluorinated polyimide solution and mixing them evenly to obtain a composite humidity sensitive solution; immersing the electrode in the composite humidity sensitive solution for dip coating to form a fluorinated polyimide composite humidity sensitive film on the electrode; and performing a film forming treatment on the fluorinated polyimide composite humidity sensitive film to obtain an electrode formed with a fluorinated polyimide composite humidity sensitive film. The drying temperature for the film forming treatment of the fluorinated polyimide composite humidity sensitive film is 150-170°C and the drying time is 100-150 min.
[0024] The preparation method of the composite humidity-sensitive material provided by the present invention uses diamine or dianhydride containing fluorine groups and hydroxyl groups as monomers and adopts a two-step synthesis method to prepare the capacitive humidity sensor using the composite humidity-sensitive material. The imidization process does not require high-temperature treatment, and the loss of water molecules from the molecular structure will not cause the film to shrink, thereby destroying the structure of the sensitive film and affecting the performance of the sensor.
[0025] The present invention also provides a fluorine-containing polyimide composite humidity-sensitive material prepared by the above-mentioned preparation method. The fluorine-containing polyimide composite humidity-sensitive material is mainly composed of a uniform mixture of fluorine-containing polyimide and nano-silicon dioxide, wherein the main chain of the polyimide is a hydrophobic skeleton and contains hydrophilic polar groups that can adsorb water molecules, such as carbonyl, carboxyl, etc. The hydrophilic polar groups have strong hydrogen bonds with the adsorbed water molecules, making it difficult for the water molecules to desorb. The introduction of hydrophobic fluorine-containing atoms into the composite humidity-sensitive material can weaken the coagulation of water molecules, reduce the density of hydrophilic groups, reduce the wet stagnation of the humidity-sensitive material, and make the capacitance output linear. At the same time, the introduction of fluorine atoms can increase the distance between molecular chains, reduce the intermolecular forces, make it easier for solvent molecules to diffuse into the material, improve the solubility performance, and improve the processability of the composite humidity-sensitive material. In addition, the introduction of silicon dioxide nanoparticles with a large specific surface area into the composite humidity-sensitive material can make the humidity-sensitive material adsorption-desorption equilibrium speed fast, accelerate the response speed, and improve the humidity sensing performance.
[0026] The present invention also provides an application of the above-mentioned fluorinated polyimide composite humidity-sensitive material in a humidity sensor. Wherein, the humidity sensor is a capacitive humidity sensor, comprising a silicon substrate, a metal electrode deposited on the silicon substrate, and a fluorinated polyimide composite humidity-sensitive material formed on the metal electrode. Preferably, a gold interdigital electrode of a silicon substrate with a spacing of 5 μm is used as a substrate, and the good solubility of polyimide is utilized to prepare an interdigital capacitive humidity sensor based on a composite of polyimide and silicon dioxide nanoparticles by a dip coating method. In this way, the fluorinated polyimide composite humidity-sensitive material is used as a humidity-sensitive film in a capacitive humidity sensor, and the humidity deviation after being treated with double 85 for 10 days does not exceed 1%, the linearity is good, the performance is better than that of traditional humidity-sensitive materials, and it has good application prospects.
[0027] The following is a specific embodiment to further illustrate the technical solution to be protected by the present invention.
[0028] Examples 1-4 Embodiments 1-4 of the present invention each provide a fluorinated polyimide composite humidity-sensitive material, which is mainly composed of a uniform mixture of fluorinated polyimide and nano-silicon dioxide, wherein the main chain of the polyimide is a hydrophobic skeleton and contains hydrophilic polar groups that can adsorb water molecules.
[0029] Each embodiment also provides a method for preparing the composite humidity-sensitive material, including the steps of: adding 3 mmol (0.932 g) of 4,4'-methylenebis(2,6-diethylaniline), 3 mmol (1.099 g) of hexafluoropropane and 9.45 mL of N-methylpyrrolidone to a three-necked flask in sequence, stirring and dissolving. Adding 6 mmol (1.0861 g) of 4,4'-oxydiphthalic anhydride twice, 10 min apart, stirring and reacting in a nitrogen atmosphere ice water bath for 24 h, adding 18 mmol (1.68 mL) of acetic anhydride and 6 mmol (0.59 mL) of 3-methylpyridine, continuing the reaction for 24 h, and precipitating the obtained product in anhydrous ethanol, vacuum drying at 80°C for 24 h after suction filtration to obtain a fluorinated polyimide solid powder. Take 0.4 g of fluorinated polyimide and dissolve it in 1.7 mL of NN dimethylacetamide, add 0.038 g, 0.04 g, 0.042 g, and 0.044 g of silica nanoparticles respectively, stir thoroughly to obtain a humidity sensitive solution, immerse the interdigital electrode in the dipping solution to deposit a humidity sensitive film, take it out and heat it at 160°C for 120 min, and the above-mentioned fluorinated polyimide composite humidity sensitive film can be formed on the interdigital electrode.
[0030] That is, the mass ratios of fluorinated polyimide and nano-silicon dioxide in the composite humidity-sensitive materials of Examples 1-4 are 10:0.95, 10:1, 10:1.05, and 10:1.1; other parameters and processes remain unchanged.
[0031] The EDS image of the composite humidity sensitive material prepared in Example 2 is as follows: Figure 1 As shown. Figure 1 It can be observed that the composite humidity-sensitive material contains elements such as F and Si, indicating that the method provided in this embodiment successfully synthesizes a fluorinated polyimide composite humidity-sensitive material including silicon dioxide.
[0032] Comparative Example 1 provides a polyimide composite humidity-sensitive material, and its preparation method is basically the same as the preparation method provided in Example 2, the main difference being that hexafluoropropane is omitted in this comparative example, and the amount of 4,4'-methylenebis(2,6-diethylaniline) is increased to 6 mmol, and other parameters and process steps remain unchanged.
[0033] Comparative Example 2 provides a polyimide composite humidity-sensitive material, and its preparation method is basically the same as the preparation method provided in Example 2, except that: in this comparative example, 4,4'-methylenebis(2,6-diethylaniline) as a diamine is omitted, and the amount of hexafluoropropane is increased to 6 mmol, and other parameters and process steps remain unchanged.
[0034] Comparative Example 3 provides a fluorinated polyimide humidity-sensitive material, and its preparation method is basically the same as the preparation method provided in Example 2, with the main difference being that the addition of nano-silicon oxide is omitted in this comparative example, and other parameters and process steps remain unchanged.
[0035] application Each of Application Examples 1-7 of the present invention is a capacitive humidity sensor, comprising: a silicon substrate, gold interdigital electrodes deposited on the silicon substrate, and a fluorinated polyimide composite humidity-sensitive film formed on the interdigital electrodes by dip-coating, wherein the spacing between the gold interdigital electrodes is 5 μm, and the fluorinated polyimide composite humidity-sensitive film formed in Application Examples 1-7 is formed on the corresponding interdigital electrodes by dip-coating of the fluorinated polyimide composite humidity-sensitive material provided by the corresponding Embodiments 1-7.
[0036] The main difference between application examples 1-3 and application example 2 is that application examples 1-3 use the humidity-sensitive materials provided by comparison examples 1-3 to replace the fluorinated polyimide composite humidity-sensitive material provided by example 2, and other structures and methods are different.
[0037] Performance Testing (1) Effect of diamine on fluorinated polyimide composite humidity-sensitive materials The main difference between the humidity sensitive materials provided in Example 2, Comparative Example 1 and Comparative Example 2 is that in the preparation process, the amount of 4,4'-methylenebis(2,6-diethylaniline) as a diamine and hexafluoropropane as a fluoride is different. The amount of diamine and fluoride used has an important influence on the hysteresis performance of the humidity sensitive material. The capacitive humidity sensors of Application Example 2, Application Comparative Example 1 and Application Comparative Example 2 were used to test the humidity response performance. The test results are as follows: Figure 2 shown.
[0038] from Figure 2 It can be seen that the fluorinated polyimide composite humidity-sensitive material provided in Example 2 has a high response sensitivity, good response linearity, and small hysteresis. Figure 2 a), Comparative Example 1 ( Figure 2 b) and Comparative Example 2 ( Figure 2 c) The capacitance of the sensor of the provided hygroscopic material in the dehumidification process is greater than that in the hygroscopic process, because after the external water molecules enter the polyimide, it will be difficult to desorb due to condensation, physical adsorption and chemical adsorption. During the dehumidification process, the polyimide contains more water molecules, resulting in a larger output capacitance. The introduction of hydrophobic fluorine-containing groups during the synthesis process can inhibit the aggregation of adsorbed water molecules to form clusters that are difficult to remove, ensure that it has a relatively balanced adsorption-desorption response time, and reduce hygroscopicity. Therefore, the embodiment of the present invention uses hexafluoropropane and diamine in combination to make the performance of the composite hygroscopic material better.
[0039] (2) Effect of silicon dioxide dosage on fluorinated polyimide composite humidity-sensitive materials The amount of nano-silicon dioxide used has an important influence on the hysteresis performance of the fluorinated polyimide composite humidity sensitive material. The following humidity response performance test is carried out using the capacitive humidity sensors provided in Application Examples 1-4 and Comparative Example 3 as the objects. The test results are as follows: Figure 3 shown.
[0040] from Figure 3 It can be seen that as the amount of nano-silicon dioxide increases, the capacitance value also increases. When the mass ratio of fluorinated polyimide to nano-silicon dioxide is 10:1 (Application Example 2), the linearity of the response curve is the best, and the capacitance value is significantly improved compared with the application of Comparative Example 3, indicating that the sensor has better humidity sensitive response characteristics after composite. Therefore, the mass ratio of fluorinated polyimide to silicon dioxide is preferably 10: (0.95-1.05), among which the humidity response of the humidity sensor is best when the mass ratio is 10:1.
[0041] (3) High temperature and high humidity stability The capacitive humidity sensors provided in Application Example 2, Application Comparative Example 1 (without fluorine) and Application Comparative Example 3 (without silicon dioxide) were used as the objects to test the humidity response performance in a high temperature and high humidity environment using the following method. The test results are as follows: Figure 4 Among them, the high temperature and high humidity test method: the prepared capacitive humidity sensor is placed in an environment of 85% RH (humidity) and 85°C for ten days, and the test humidity deviation results are as follows Figure 4 shown.
[0042] Figure 4 The results show that by comparing the initial humidity deviation and the humidity deviation after high temperature and high humidity treatment, it is found that the humidity deviation of the capacitive sensor provided by the application embodiment does not exceed 1%. Figure 4 It can be seen that compared with the application of comparative example 1 ( Figure 4 b) and 3 ( Figure 4 c) compared to the application example 2 ( Figure 4 a) The fluorinated polyimide composite humidity-sensitive material provided in Example 2 is used as the humidity-sensitive film of the capacitive humidity sensor. After high temperature and high humidity treatment, its humidity response does not show a significant difference, and only shows an offset in a high humidity environment. The calculated offset value is less than 1%. This is mainly because the polyimide synthesized in the embodiment of the present invention is based on a diamine or dianhydride having a fluorinated group and a hydroxyl group as a monomer. The strong hydrophobicity of fluorine atoms can reduce the water absorption rate of polyimide. At the same time, the process of preparing the sensor does not require high-temperature imidization, and will not damage the structure of the sensitive film and affect the performance of the sensor. Therefore, the preparation method provided in the embodiment of the present invention can effectively improve the problem that the polyimide material is easily hydrolyzed in a high temperature and high humidity environment, which is beneficial to improving the high humidity stability of the polyimide.
[0043] Therefore, the fluorinated polyimide composite humidity-sensitive material prepared by the preparation method provided in the embodiment of the present invention is used as a humidity-sensing film of a capacitive humidity sensor, which has better linear response and accuracy, can effectively improve the measurement accuracy, stability and reliability of the humidity sensor, and can effectively improve the problem of decreased product stability of humidity sensor products on the market after working for a long time in a high temperature and high humidity environment. It can be applied to more harsh environments, such as large-scale manufacturing industries such as the pharmaceutical industry and the food industry.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for preparing a fluorinated polyimide composite humidity-sensitive material, comprising the steps of: Synthesis of polyamic acid: dissolving diamine, dianhydride and fluoride in a non-protonic polar solvent, and subjecting the dianhydride, diamine and hexafluoropropane to a low-temperature polycondensation reaction under a nitrogen atmosphere to obtain a polyamic acid solution, wherein: The fluoride is hexafluoropropane, 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane, 2,2'-bis(trifluoromethyl)diaminobiphenyl; Chemical imidization: adding a catalyst to the polyamic acid solution to continue the reaction to obtain a fluorinated polyimide powder; Preparation of the composite humidity-sensitive material: dissolving the fluorinated polyimide powder in an organic solvent, adding silicon dioxide nanoparticles and mixing thoroughly to obtain the composite humidity-sensitive material.
2. The preparation method according to claim 1, characterized in that The mass ratio of the fluorinated polyimide powder to the silicon dioxide nanoparticles is 10: (0.95-1.05).
3. The preparation method according to claim 1 or 2, characterized in that The step of synthesizing the polyamic acid comprises: first dissolving the diamine and 2,2-bis(3-amino-4-hydroxyphenyl)-bishexafluoropropane in the aprotic polar solvent, then adding the dianhydride in multiple times, with the time interval between two adjacent additions of the dianhydride being 5-15 minutes, stirring the reaction in a nitrogen atmosphere ice water bath for 22-24 hours to synthesize the polyamic acid, and obtaining the polyamic acid solution; Preferably, the temperature of the ice water bath is 0-5°C.
4. The preparation method according to claim 3, characterized in that The molar ratio of the diamine, the dianhydride and the fluoride is 2:1:(0.95-1.05).
5. The preparation method according to claim 3, characterized in that: The diamine is 4,4'-methylenebis(2,6-diethylaniline), 4,4'-biphenylenediamine or p-phenylenediamine.
6. The preparation method according to claim 3, characterized in that: The dianhydride is 4,4'-oxydiphthalic anhydride, pyromellitic dianhydride, benzophenone tetracarboxylic dianhydride or biphenyl tetracarboxylic dianhydride.
7. The preparation method according to any one of claims 1 or 2 or 4 to 6, characterized in that: The chemical imidization step comprises: adding the catalyst to the polyamic acid solution, continuing to stir the reaction in a nitrogen atmosphere ice water bath for 22-24 hours to fully imidize the polyamic acid, adding anhydrous ethanol to obtain a light yellow viscous product; filtering and vacuum drying the light yellow viscous product to obtain the fluorinated polyimide powder; Preferably, the vacuum drying temperature is 70-100°C; Preferably, the catalyst is acetic anhydride and 3-methylpyridine in a molar ratio of (2.5-3.5):
1.
8. The preparation method according to claim 1 or 2, characterized in that: The steps of preparing the composite humidity sensitive material include: dissolving the fluorinated polyimide powder in the organic solvent to form a fluorinated polyimide solution; adding the silicon dioxide nanoparticles to the fluorinated polyimide solution and mixing them uniformly to obtain a composite humidity sensitive solution; immersing an electrode in the composite humidity sensitive solution for dip coating to form a fluorinated polyimide composite humidity sensitive film on the electrode; and drying and film-forming the fluorinated polyimide composite humidity sensitive film to obtain an electrode formed with the fluorinated polyimide composite humidity sensitive film. Preferably, in the drying film-forming process, the drying temperature is 150-170°C and the drying time is 100-150 min; Preferably, the particle size of the silicon dioxide nanoparticles is 20-50 nm; Preferably, the solid-liquid ratio of the fluorinated polyimide powder to the organic solvent is 1: (4-5) g / mL.
9. A fluorinated polyimide composite humidity-sensitive material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the fluorinated polyimide composite humidity-sensitive material according to claim 9 in preparing a humidity-sensitive sensor; Preferably, the humidity sensor comprises a metal electrode, and the fluorinated polyimide composite humidity sensitive film is subjected to a film-forming process by a dip coating method to form a humidity sensitive film on the metal electrode; Preferably, the humidity sensor is a capacitive humidity sensor.
Citation Information
Patent Citations
Capacitive humidity sensor and preparation method thereof
CN115201284A
Fluorine-containing polyimide humidity-sensitive capacitor and preparation method therefor
CN105001778A
Humidity-sensitive biphenyl polyimide capacitor and making method thereof
CN105111439A
Modified polyimide humidity-sensitive coating as well as preparation method and application thereof
CN118725730A
Method for Manufacturing Humidity Sensor by usingPorous Silicon Layer and Sensor Manufactured by it
KR1020060021082A